2007
DOI: 10.1007/s11270-007-9581-z
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Modeling of Sand-Bentonite Cover for ARD Mitigation

Abstract: This paper deals with field measurements and hydraulic, oxygen transport and geochemical speciation modeling undertaken to evaluate the performance of a sand-bentonite test cover overlying a 20% sloping waste rock platform. A pit run (gravelly sand) layer protected the sand-bentonite layer. The study site was the Whistle Mine near Capreol, Ontario, Canada. The purpose of the study was to evaluate a number of test covers and select a final cover for the decommissioning of 7 million tonnes of acid-generating was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The lack of a significant increase in discrete acidity or SO 4 loads for the fortnightly leached column when compared with the weekly leached column suggests that oxidation was largely inhibited during the second week, where lower water contents prevailed. This result concurs with observations by Song and Yanful (2008) that more frequent flushing increases overall oxidation rate specifically because it exposes fresh sulphide surfaces to oxidation more often. The longer residence time may also increase the import of aluminosilicate neutralisation reactions in a waste rock dump context, enabling them to react to a greater extent and buffer system pH more than would otherwise have been the case.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The lack of a significant increase in discrete acidity or SO 4 loads for the fortnightly leached column when compared with the weekly leached column suggests that oxidation was largely inhibited during the second week, where lower water contents prevailed. This result concurs with observations by Song and Yanful (2008) that more frequent flushing increases overall oxidation rate specifically because it exposes fresh sulphide surfaces to oxidation more often. The longer residence time may also increase the import of aluminosilicate neutralisation reactions in a waste rock dump context, enabling them to react to a greater extent and buffer system pH more than would otherwise have been the case.…”
supporting
confidence: 92%
“…Reducing flushing volume and frequency is likely to prevent the exposure of fresh sulphide mineral surfaces to oxidation, potentially decreasing solute load (Song and Yanful, 2008). The long-term oxidation of a sulphidic waste rock dump can therefore be reduced through decreased infiltration, which effectively spreads acid generation from these wastes over a longer time period and reduces the requirement for treatment of acidic water (Song and Yanful, 2008). The increased residence time caused by a decrease in flushing frequency also enables greater participation of aluminosilicate neutralising minerals in determining drainage quality (Adu-Wusu, 2005, in Song andYanful, 2008).…”
Section: = P -R -δS -Etmentioning
confidence: 99%
“…Since the Mattabi Mine is closed and no precipitation data was available, site data from the Whistle Mine ͑near Capreol, Ont.͒, was used as a guide. Using the Whistle site data also allowed us to compare our current results to those reported by Song and Yanful ͑2008͒. This specific laboratory case had the same setup procedure, equipment, and waste rock as those of the column tests described above. The case was labeled as Column 1 and had the following characteristics: height of the water rock= 25 cm and dry density = 2.06 g / cm 3 .…”
Section: Experimental Setup and Measurementsmentioning
confidence: 91%
“…The column materials, which consisted of organic carbon and zero valence iron (ZVI), Containment. Song and Yanful (2008) examined the effectiveness of a sand-bentonite cover overlying a 20% sloping waste rock platform to mitigate acid rock drainage (ARD) by using field measurements and hydraulic, oxygen transport, and geochemical speciation modeling to evaluate its performance. Modeling of the process showed that decreasing the oxygen flux with the sand-bentonite cover could minimize sulfide oxidation and acid generation in the waste rock, and aqueous speciation modeling also suggested that the A detailed critical analysis of the waste management strategies adopted in two uranium production centres in Brazilwas presented by Fernandes et al (2008).…”
mentioning
confidence: 99%